Disability and Poverty Among Persons with Disabilities: The Role of the Church - Nyongesa, Gregory Jumah (Abdul Media Literasi, 2024)
People with disabilities (PWDSs) are usually left out of the mainstream education and socio-economic activities. These include those with sensory, physical, and cognitive disabilities. The United Nation's Convention on the Rights of Persons with Disabilities (2006) and Kenya's Persons with Disabilities Act (2004) address issues affecting PWDSs to promote, protect, and ensure the full and equal enjoyment of human rights and fundamental freedoms, promote respect for their dignity as well as facilitate the full participation in all sectors of society. Despite these efforts, PWDSs continue to be marked by experiences of discrimination, prejudice and inequality. Religion and Theological interpretations of disability have significantly shaped the ways in which society relates to PWDSs thereby reinforcing marginalization and exclusion in the social, economic, political, educational and religious life of the society. This presentation is derived from a study on promoting awareness and participation of PWDSs in education and other community-based programs in Siaya County. This action research study investigated the relationship between poverty and Disability from the perspective of PWDSs. Data was collected using focus group discussions and interviews. The main finding was that PWDSs are living in poverty, which they attribute to being disabled. The church, perceived to have a role to play in community welfare did not seem to have a structured way of identifying or providing for PWDSs, who are incidentally members of their churches. In matters of education, it was found that there are many children with disabilities out of school that members of the clergy were aware of but seemed to have no way of engaging stakeholders to support them. Misinterpretation of religious teachings seemed to have a bearing on how PWDSs were perceived. It is recommended that the church should take active role in identifying and engaging relevant stakeholders in providing services, including education, for PWDS.